2017
DOI: 10.12911/22998993/76830
|View full text |Cite
|
Sign up to set email alerts
|

Production of Biodiesel from Local Available Algae in Jordan

Abstract: The present study aims at producing diesel out of algae. The production of biodiesel was performed at Tafila Technical University laboratories. The algae were brought from Almansora stream at Tafila governorate-Jordan and afterwards dried in an oven at 80 ºC for 12 hours. The dried algae were ground using disc mill until powder was obtained. The powdered algae underwent a distillation process with the addition of iron sulphate hydrate to the algae using a distillation column in order to extract the oil. Methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Aljabarin et al [26] studied the production of biodiesel from algae. The algae were taken from open ponds and then dried for 12 hours in the oven at 80 °C.…”
Section: Figure (2) Algal Biofuel Pipelinementioning
confidence: 99%
“…Aljabarin et al [26] studied the production of biodiesel from algae. The algae were taken from open ponds and then dried for 12 hours in the oven at 80 °C.…”
Section: Figure (2) Algal Biofuel Pipelinementioning
confidence: 99%
“…In 2017 Aljabarin et al after algae drying and oil extraction from it, produced biodiesel and concluded that the biodiesel properties are similar to diesel oil, except that it reduces CO2 emissions and doesn't emit any SO 2 sulfur [15]. Ge et al…”
Section: Introductionmentioning
confidence: 99%